Peer support specialists and perinatal opioid use disorder: Someone that's been there, lived it, seen it. (March 2020) - Fallin-Bennett, Amanda; Elswick, Alex; Ashford, Kristin
Highlights: Peer support specialists positively impact perinatal women's recovery from opioid use disorder. Clearer boundaries are needed between peer support specialists and clients. More research is needed on the impact of peer support on sustained recovery for perinatal women. Abstract: Perinatal opioid use disorder (OUD) has increased drastically since 2000 and is associated with myriad adverse outcomes. The Substance Abuse and Mental Health Services Administration (SAMHSA) recommends using peer support services to promote sustained remission from substance use disorders (SUDs). Integrating peer support specialists into perinatal OUD treatment has the potential to improve maternal and child health. However, there is limited published research on the experiences of pregnant and parenting women with peer support specialists during SUD treatment. The purpose of this study was to: (1) describe experiences of perinatal women undergoing OUD treatment with peer support specialists; (2) describe recommendations for improving or enhancing peer support services. For this qualitative descriptive study, we conducted two focus groups in a private location in a clinic that serves postpartum women with OUD ( N  = 9) who were parenting a child under the age of 5. The focus groups were voice recorded, professionally transcribed, and analyzed in MAXQDA using content analysis. Four themes emerged from the data: Feeling Supported by Peer Support Specialists, Qualities of an 'Ideal' Peer Support Specialist, Strategies to Improve Interactions with Peer Support Specialists, and Importance of Communication Across the Perinatal Period. Participants reported that PSSs had a strong, positive impact on their recovery. Postpartum women report overall positive experiences receiving peer support services during their pregnancy and postpartum period. However, participants offered suggestions to improve their interactions with PSSs, such as clarifying the boundaries between peer supporters and clients. Pregnant and postpartum women in OUD treatment have the potential to benefit from access to PSS throughout their perinatal period. Future research is needed to determine the impact of PSS on sustained recovery for perinatal women with OUD.